Contraction and expansion dynamics: deciphering genomic underpinnings of growth rate and pathogenicity in Mycobacterium - Zhu, Xiaoying; Lu, Qunfeng; Li, Yulei; Long, Qinqin; Zhang, Xinyu; Long, Xidai; Cao, Demin (Frontiers in Microbiology, 2023)
Background Mycobacterium bacteria, encompassing both slow growth (SGM) and rapid growth mycobacteria (RGM), along with true pathogenic (TP), opportunistic pathogenic (OP), and non-pathogenic (NP) types, exhibit diverse phenotypes. Yet, the genetic underpinnings of these variations remain elusive. Methods Here, We conducted a comprehensive comparative genomics study involving 53 Mycobacterium species to unveil the genomic drivers behind growth rate and pathogenicity disparities. Results Our core/pan-genome analysis highlighted 1,307 shared gene families, revealing an open pan-genome structure. A phylogenetic tree highlighted clear boundaries between SGM and RGM, as well as TP and other species. Gene family contraction emerged as the primary alteration associated with growth and pathogenicity transitions. Specifically, ABC transporters for amino acids and inorganic ions, along with quorum sensing genes, exhibited significant contractions in SGM species, potentially influencing their distinct traits. Conversely, TP strains displayed contraction in lipid and secondary metabolite biosynthesis and metabolism-related genes. Across the 53 species, we identified 26 core and 64 accessory virulence factors. Remarkably, TP and OP strains stood out for their expanded mycobactin biosynthesis and type VII secretion system gene families, pivotal for their pathogenicity. Conclusion Our findings underscore the importance of gene family contraction in nucleic acids, ions, and substance metabolism for host adaptation, while emphasizing the significance of virulence gene family expansion, including type VII secretion systems and mycobactin biosynthesis, in driving mycobacterial pathogenicity.